The Influence of BUMDes, Village Funds, and PADes on SDGs in Tourism Village of Kudus Regency - Kunasari, Kunasari; Sukardi, Agung Slamet (PUBLIKA : Jurnal Ilmu Administrasi Publik, 2026)
The focus of this study is to understand the impact of Village Owned Enterprises (BUMDes), Village Funds, and Village Owned Assets (PADes) on the achievement of the Sustainable Development Goals (SDGs) in tourist villages in Kudus Regency. This study employs a quantitative method with a non-probability sampling approach, specifically incidental sampling, and the sample size was calculated using the Lemeshow formula. Consequently, a questionnaire was distributed to the Kudus community with a total of 100 respondents, and SPSS version 20 was used to analyze the data. The variables were BUMDes (X1), Village Fund (X2), PADes (X3), and SDGs (Y). After testing these variables, the results of this study indicate that the BUMDes variable has a positive influence on the Sustainable Development Goals (SDGs) variable. Furthermore, the Village Fund variable has a significant influence on the Sustainable Development Goals (SDGs) Achievement variable in Tourism Villages in Kudus Regency. Meanwhile, the PADes variable has not yet been able to significantly influence the Sustainable Development Goals (SDGs) Achievement variable in Tourism Villages in Kudus Regency. This study aims to provide insights into the contribution of Village-Owned Enterprises (BUMDes) that play a role in the SDGs, and demonstrates that the Village Fund plays a very important role in the SDGs. Consequently, sustainable development can proceed as planned. However, this study also indicates that PADes has not yet had an impact on the SDGs.